Why Do Some Sharia Food Firms Outperform Others in Indonesia’s Stock Market (2019–2023)? - Nofrianto; Nadhifah Adiratna; Eli Suryani (UPT Publikasi Ilmiah UNISBA, 2026)
Fluctuations in stock returns encourage investors to identify the financial indicators that most effectively explain company performance. However, evidence on Sharia-compliant food and beverage firms remains limited, particularly regarding the simultaneous effects of multiple financial ratios. This study examines the influence of the Current Ratio (CR), Debt-to-Equity Ratio (DER), Total Asset Turnover (TATO), Return on Equity (ROE), Price-to-Earnings Ratio (PER), Price-to-Book Value (PBV), and Market Value Added (MVA) on the stock returns of food and beverage companies listed in the Indonesia Sharia Stock Index (ISSI) during 2019–2023. Using panel data from annual reports and financial statements published by the Indonesia Stock Exchange, the study applies multiple regression analysis to evaluate both simultaneous and partial effects. The findings reveal that all seven financial ratios jointly have a significant effect on stock returns. Individually, only ROE and PER significantly influence stock returns, whereas CR, DER, TATO, PBV, and MVA show no significant effects. These findings indicate that profitability and market valuation are the primary financial indicators associated with stock returns in Sharia-compliant food and beverage firms. The results provide practical implications for corporate managers to strengthen profitability and for investors to prioritize ROE and PER when evaluating investment opportunities in the Indonesian Sharia capital market.